A break-even analysis of orbital debris and space preservation through monetization. Issue 4 (December 2022) - Zhu, Martin K
Abstract: While NASA and European Space Agency (ESA) publicly recognize space debris imposes high costs on space economies, they have not published monetized space debris costs. This study monetizes the increasing costs of orbital debris and costs of space preservation through Monte Carlo simulations using a break-even analysis.  Orbital debris imposes satellite fortification, avoidance, and early replacement costs on satellite owners. This paper assigns values to NASA published space debris mitigation models for an estimate of space preservation costs. Estimating space debris costs has been hampered by a lack of information largely due to commercial proprietary information. This study shows how simple-realistic assumptions can turn sparse data into the basis of a robust analysis. Further, by conducting a break-even analysis of these cost streams, this study identifies the global cost savings after the costs of space debris equals the costs of space preservation. Using alternative inputs, this study conducts sensitivity analyses to identify the effectiveness of mitigation and remediation options. At a 90% success rate of post-mission disposal (PMD) and an active removal of as few as 5 defunct spacecraft per year are the sufficient and effective space preservation measures if spacefaring communities are in compliance with them sooner rather than later. Phases and timelines for global practicing measures of mitigation and remediation are sensitive to the outcome of break-even analysis. In conclusion, spacefaring communities need to stabilize the space debris environment for cost-savings and space sustainability. A simple solution is post-mission disposal and a worldwide orbital user sinking fund per launch to finance future debris removal and hedge preservation timeline uncertainty.active debris removal missions per year that proposed by NASA ODPO would cost less than one third the costs of space debris under the status quo.